El derecho de las niñas, niños y adolescentes a acceder a una justicia especializada y las unidades judiciales multicompetentes - Dier Lozada, Nathaly Patricia (2024)
The present research work entitled “the Rights of girls, boys and teenagers to access specialized justice and the Multicompetent Judicial Units” seeks to analyze the discrepancy between the operation of the Multicompetent Judicial Units and the constitutional precept that guarantees access to a Specialized Justice for boys, girls and teenagers, according to Art 175 of The Constitution of the Republic of Ecuador. The main objective of the Research is to determine the impact of the Resolutions adopted by the Multicompetent Judges regarding the right of children to access specialized justice that guarantees their rights. A legal antinomy is identified between the Carta Magna and the Organic Code of the Judicial Function because the Multicompetent Judicial Units do not accomplish with the principle of specialty necessary to protect the rights of minors. This lack of specialization has generated problems in administration of justice by addressing various matters without the required specialty in the field of childhood and adolescence; Therefore, it is important to ensure the right of access to specialized justice for children and adolescents in order to comply with the Constitutional Mandate. The Methodology developed in this research a mixed method, in which interviews were carried out with the Judges of the Multicompetent Judicial Unit based in Pelileo Canton, As well as the analysis of sentences from these Multicompetent Units and interviews with the Lawyers of Tungurahua. It is concluded that, although these Units guarantee access to Justice, the lack of access to specialized justice limits the comprehensive knowledge necessary to fully protect the rights of minors, and also compromises compliance with other fundamental principles, which constitutes a clear violation of their rights such as Legal Security. Therefore, it is necessary to create Specialized Judicial Units in places where Multicompetence in maintained in order to effectively protect the rights of girls, boys and adolescents